The dissemination and implementation of trauma-focused cognitive behavioural therapy for children and adolescents in seven European countries - Pfeiffer, Elisa; Unterhitzenberger, Johanna; Enderby, Pia; Juusola, Aino; Kostova, Zlatina; Lindauer, Ramon J. L.; Nuotio, Sanna-Kaija; Samuelberg, Poa; Jensen, Tine K. (BMC, 2025)
Background
There is broad scientific evidence for the effectiveness of individual trauma-focused evidence-based treatments (EBTs) such as "trauma-focused cognitive behavioural therapy" (TF-CBT) for children and adolescents with posttraumatic stress symptoms. However, there is a significant research-to-practice gap resulting in traumatized children in high-income countries in Europe having only very limited access to these treatments. The aim of this study was, therefore, to identify common barriers and successful dissemination and implementation (D&I) strategies of evidence-based trauma-focused treatments (in particular TF-CBT) in seven European countries.
Methods
For this study, we chose a mixed-method approach: an online survey among certified European TF-CBT trainers (N = 22) and the collection of country-based narratives from TF-CBT experts in different European countries (Finland, Germany, Italy, Netherlands, Norway, Sweden).
Results
Common modifiable barriers to the implementation of TF-CBT were identified on different levels (e.g. government or treatment level), and successful D&I strategies were highlighted across all countries, such as translations of materials. Additionally, the experts from the country narratives put together a broad overview of TF-CBT research in Europe.
Conclusions
The results of this study revealed that especially learning collaborations and the development of joint European efforts in funding and researching D&I strategies are crucial for future implementation of trauma-focused EBTs in Europe.